KONSELING MELALUI TULISAN SEBAGAI ALTERNATIF STRATEGI KONSELING REMAJA BAGI GURU BK DI SMA - Farida Harahap (Paradigma, 2010)
This article discusses writing counseling technique which would be conducted by school counselors as a way in enhancing the effectiveness of direct services for students. Writing is an effective therapeutic tool which has been well documented and written therapeutic letters specifically has shown as a high positively effect tool. Recommendations are provided for school counselors who might implement this technique for students.Keywords : writing, counseling, adolescence, school counselor